Association between pre‐donation serum uric acid concentration and change in renal function after living kidney donation in women. Issue 12 (December 2014) - Cho, A.; Lee, J. E.; Jang, H. R.; Huh, W.; Kim, D. J.; Oh, H. Y.; Kim, Y.‐G.
Abstract Background Reduction in renal mass after unilateral nephrectomy causes functional and structural changes in the remaining kidney. Aim We aimed to investigate the association between pre‐donation serum uric acid (SUA) concentration and the change in renal function after living kidney donation. Methods This retrospective study included 413 living kidney donors from a single centre. We collected medical history and laboratory findings at baseline and 6 months after donation. Renal function was assessed by calculating the estimated glomerular filtration rate (eGFR) using the Chronic Kidney Disease Epidemiology Collaboration equation. Main outcomes were the percentage change in eGFR from before to 6 months after donation and the percentage of patients whose eGFR decreased by >25% after donation compared with the pre‐donation baseline value. Results Mean age was 40 ± 11 years, and eGFR was 106 ± 14 mL/min/1.73 m2. In women, the SUA concentration was linearly associated with the change in eGFR after donation independently of baseline eGFR (standardised coefficient – 0.16, P = 0.04). Multiple logistic analysis showed that a 59.5 μmol/L increase in baseline SUA concentration was associated with a 1.7‐fold higher risk of a > 25% decrease in eGFR after donor nephrectomy (95% confidence interval, 1.2–2.5; P = 0.007) in women. In contrast, SUA concentration was not an independent risk factor of decrease in eGFR after donor nephrectomy in men. Conclusions Pre‐donation SUA concentration is associated independently with the change in renal function after donor nephrectomy in women but not in men.